The self and students’ mental health: integrating spirituality and islamic education - Luluk Ifadah; Dwi Indah Rahmawati; Natasya Aulia; Mia Surya Fatzila; Nishvi Launi Hasna Kamalia; Ahmad Aji Pangestu; Amel Grasine Farona (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the relationship between the Spiritual Emotional Freedom Technique (SEFT) and students’ mental health within the framework of harmonizing spirituality and Islamic education. The research uses a descriptive qualitative approach through field studies, observations, interviews, and documentation as data collection techniques. The findings indicate that the implementation of SEFT assists students in managing emotional stress, enhancing inner peace, and cultivating religious attitudes that positively impact their mental well-being. The integration of SEFT with Islamic educational values such as patience, sincerity, and reliance on God (tawakkul) has been shown to strengthen students’ psychological resilience in facing life challenges. Therefore, SEFT emerges as a strategic alternative in efforts to improve spiritual-based mental health in Islamic educational settings.